Ativos intangíveis: uma perspectiva teórica para o seu reconhecimento e mensuração nas demonstrações contábeis - Eduardo José Zanoteli (2015)
Social, economic and production changes experienced from the twentieth century on, which extend up to and perhaps beyond the twenty-first century, led humanity to the Information Age, resulting in a serious anomaly on the Accounting Science caused by not recognizing and measuring intangible assets, considered the most valuable assets of this new era. Because this anomaly was not discussed neither in Normative nor in Positive Accounting Researches, the result was a representation crisis of financial statements, which eroded their explanatory power and reduced their usefulness for both external and internal users. This thesis is one of the first attempts to address this crisis, trying to deal with its causes and not its effects, which presents philosophical and theoretical questions rarely discussed in accounting, as a result of the dominant paradigm, namely, positivism among the scientific community and historical cost among the professional community. In this regard, the general objective of this research is to propose a theoretical perspective for recognizing and measuring intangible assets in accounting statements, which proved possible only by a comprehensive review and mediation of the philosophical and theoretical bases of Accounting paradigms. Therefore, an extensive literature review aiming to get a proper philosophical and theoretical framework which is properly integrated with field research (i.e. integrating reason with experience) allowed for a new theoretical perspective, which is the essence this thesis. Thus, a multi-case study along with the triangulation by experts, both aligned to the philosophical and theoretical framework, were carried out, resulting in a theoretical perspective that was finally subjected to an empirical application by analysing statistically the sample of the multi-case study. In essence, the theoretical perspective proposed in this thesis has confirmed the following assumptions: the recognition of both anomalies and the accounting crisis; the opening to the commensurability between the paradigms of science and the accounting professional practice; the realignment of the concept objectivity-reliability; the reduction of the excess of accounting conservatism; the recognition and measurement of intangible assets in the balance sheet; better disclosure of accounting information that extends beyond the limits and boundaries of the financial statements; and an integrated application of the evaluating, controlling and legal accounting functions. At the end of this study, it is concluded that the proposed theoretical perspective presents Accounting researchers and practitioners with a paradigm shift that will require much time and persuasion; because, as taught Kuhn (2011 [1962]), this is not done by a single man and never overnight.